Strategi Pemasaran Dalam Meningkatkan Penjualan Di Pasar Terubuk Bengkalis - Candri, Kiki (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
A marketing strategy is a comprehensive, integrated and integrated plan in the field of marketing that provides guidance on the activities that will be carried out to achieve goals. The aim of this research is to find out marketing strategies to increase sales at Terubuk Bengkalis Market. This type of research is qualitative. The method used in this research is the SWOT approach method. Based on the final results obtained in IFAS and EFAS, the strength factor is 2.73, the Weakness Factor is 3.41, the Opportunity Factor is 3.48, and the Threat factor is 3.41